Building services in facility management - Nurul Shahira, Arbain (2018)
Facilities management (FM) usually is difficult and complicated work. The facility staffs usually use paper or information system to record the facilities maintenance work. However, it is not easy for facility staffs to refer the traditional 2D CAD-based information illustration in the facility maintenance. Moreover, the information of same facilities maintenance needs to repeat the record and cause inconvenience for facility staffs. To overcome these problems, the building information modelling (BIM) approach is applied and developed as 3D information models for managing and maintaining facilities in the study. With the integration of BIM model with related information of facilities maintenance, the facility staffs may improve the efficiency of maintenance and management work of facilities. This study proposes a facility management (FM) based on building information modelling system for facility managers and staffs. The system is then applied in selected case study of a Kolej Kediaman 4 (KK4) to verify our proposed methodology and demonstrate the effectiveness of tracking and managing the related maintenance information in the 3D environment. Finally, this study will present the benefits, limitations and conclusions of BIM application in facilities management, and also provide suggestions for future research.